From Couch to Poll: Media Content and the Value of Local Information - Mathias Bühler; Andrew Dickens; Andrew C. Dickens (Center for Economic Studies and ifo Institute (CESifo), 2024)
We document the importance of local information in mass media for the political engagement of citizens and accountability of politicians. We study this in the context of Canada, where until 1958, competition in television markets was suppressed—Canadians received either public or private television content, but never both. While public television provided national-level informational content, private television content was distinctly local and more politically relevant to voters. We find that the introduction of television reduced voter turnout, but that this effect is exclusive to public television districts. Our findings qualify existing knowledge about the political effects of the rollout of new media, by allowing the informational content to vary while holding the media type constant. We support our argument with evidence from parliamentary debates: politicians from districts with private television are more likely to speak and act on behalf of their constituents in Parliament. Our findings thus suggest that politicians are held accountable by relevant media content.
Keywords: D72; L82; N42; N92; 330; media content; television; voting; political engagement; political accountability; natural language processing